Xanthogranulomatous endometritis mimicking endometrial carcinoma: A case report and review of literature - Du, Xiao-zhou (Radiol Case Rep, 2018)
Xanthogranulomatous endometritis (XGE) is an extremely rare chronic inflammatory condition, which may be associated with endometrial hyperplasia, endometrial carcinoma, or cervical stenosis. Imaging features can be easily misdiagnosed as an aggressive malignancy. We present a case of XGE, which is the first case of XGE with serial multimodality imaging examinations, in addition to clinical, surgical and pathologic correlations. As such, this unique case illustrates the evolution of this rare disease.